Seasonal prematurity, perinatal mortality and deficiency of serum folic acid in pregnant women - N. D. Gasanova (IRBIS LLC, 2020)
Aim: to assess the seasonality of prematurity, stillbirth, perinatal mortality and deficiency of serum folic acid in pregnant women at the Gyanja Perinatal Center (Gyanja, Azerbaijan).Materials and Methods. In 2016, 3,221 pregnant women were hospitalized at gestational age of at least 22 full weeks or more. A case of hospitalization for obstetric care of pregnant women at gestation age of 22 full weeks was used as a unit of statistical observation. All female patients were stratified in accordance of hospitalization date by calendar months and annual seasons. In each season (winter - January, spring - April, summer - July, autumn - October) in 50 pregnant women at trimester I and III (8 groups of pregnant women) serum folic acid, homocysteine, С-reactive protein, fibrinogen and alkaline phosphatase were measured.Results. The smallest and largest percentage of infants with very low birth weight (< 1500 g) was among children born in January (2.28 ± 0.75 %; 95 % Cl = 0.78-3.78) and November (13.99 ± 2.49%; 95% Cl = 9.01-18.97), respectively (р < 0.01). Comparatively assessed proportion of newborns with very low body weight in the summer and winter periods (4.55 ± 0.55 % and 4.90 ± 0.51 %, respectively) confirmed lack of significant intergroup difference (р > 0.05). Stillbirth rate between infants born in the summer and winter periods differed (1.92 ± 0.36 % and 2.53 ± 0.37 %, respectively) insignificantly (р > 0.05). Seasonal change in risk of prematurity, stillbirth and perinatal mortality was associated with seasonal changes in the level of serum folic acid, homocysteine, C-reactive protein, fibrinogen and alkaline phosphatase.Conclusion. Infants born with low and very low weight, stillbirth and perinatal losses are relatively common in autumn - from September 21 till December 20.